Percepção dos predadores de ninhos e estratégias anti-predação numa comunidade de aves da Mata Atlântica do estado de São Paulo - Zima, Paulo Victor Queijo (Universidade Federal de São Carlos, 2019)
The main cause of annual variations in bird’s reproductive output is the failure of nests resulted from predation. Eggs exposed in open nests, usually have a wide range of colorations, and may coincide with the color of the nest material, which can be considered as a mimetic strategy to avoid predation. Many hypotheses have predicted that nest characteristics and the characteristics of its surroundings also affect nest predation probability, but many of these hypotheses are still poorly tested. One such hypothesis is the ''potential prey-site hypothesis''. In this work we tested the effects of egg color in nest predation, using plasticine eggs with three color patterns, in natural nests of the Blue Manakin, Chiroxiphia caudata, and we extended the theory of the''potential prey-site hypothesis'' by addressing nest-like structures in a Atlantic Forest well-preserved area. For the first experiment we used 78 abandoned nests of the Blue Manakin, 26 with each egg pattern (all white, white with brown spots, and all brown), of which 11 (14.10%) nests were depredated by visually oriented predators: (five with white eggs; four with white eggs with brown spots; and twowith brown eggs). Although there were no significant differences in the probability of predation for each color pattern, there was a growing tendency, in which white eggs had the lowest survival rate, followed by white with brown spots, and finally the all-brown eggs. To address the ''potential prey-site hypothesis'' we first tested if the Blue Manakin could select nesting sites in which nest-like structures, such as tufts of moss and deposits of debris in horizontal forks, were in higher densities, controlled to a set of covariates. Then, we evaluated if the numbers of nest-like structures in nest surroundings were correlated to nest survival, using 42 active nests. Modelings using Generalized Linear Models indicated that nest-like structures and vegetation density were the main covariates explaining nest site choice in this species. However, we found no correlations of nest-like structures to nest survival, which corroborates only partially the ''potential prey-site hypothesis''.
Perception of nest predators and anti-predation strategies in a bird community of the Atlantic Forest of the state of São Paulo
Keywords: Predação de ninhos; Comportamento do predador; Ovos de massinha de modelar; Comunidade de predadores; Local de nidificação; Ninho críptico; Comportamento de nidificação; Nest predation; Predator behavior; Clay eggs; Predator communities; Nest site; Cryptic nest; Nesting behavior; Predation avoidance; CIENCIAS BIOLOGICAS::ECOLOGIA